Surgical Decision-Making in Median Neuropathy Associated with Distal Radius Fractures - Özkan, Sezai (J Wrist Surg, 2019)
Objectives  A lack of conclusive evidence on the treatment of acute median neuropathy (AMN) in patients with distal radius fractures has led to inconsistent surgical guidelines and recommendations regarding AMN in distal radius fractures. There is a wide variation in surgical decision-making. We aimed to evaluate international differences between surgical considerations and practices related to carpal tunnel release (CTR) in the setting of distal radius fractures. Methods  We approached surgeons who were a member of the Orthopaedic Trauma Association (United States) or of the Dutch Trauma Society (the Netherlands) and asked them to provide sociodemographic information and information on their surgical practice regarding CTR in the setting of distal radius fractures. After applying our exclusion criteria, our final cohort consisted of 127 respondents. Results  Compared with Dutch surgeons, surgeons from the United States are more of the opinion that displaced distal radius fractures are at risk of developing acute carpal tunnel syndrome (ACTS), consider persistent paresthesia in the median nerve distribution after closed reduction to be a surgical emergency less often, and are more likely to perform a CTR if there are signs of ACTS in the setting of a distal radius fracture. Conclusion  A lack of conclusive evidence has led to international differences in surgical practice regarding the treatment of ACTS in the setting of distal radius fractures. Future research should guide surgeons in making appropriate evidence-based decisions when performing CTR in the setting of distal radius fractures. Level of Evidence  This is a Level V study.